Public Relations Management in Building School Image: A Case Study - Zahroh, Luluk Atirotu (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
SDI Miftahul Huda, Kedungwaru, Tulungagung is strongly committed to developing the best educational institutions. Seeing the institution's purpose, it is understood that schools must be able to improve the quality of education and optimize the participation of the community who give good opinions for the school's image. This study aims to understand the management of public relations in building the school's image. The research method used is qualitative. The data collection technique is done by interview, observation, and documentation. Data analysis used is data reduction, data presentation, and concluding. The study results indicate that the implementation of public relations in building the school's image is carried out through internal and external work programs, where each work program has a role in building the image of SDI Miftahul Huda. Public relations strategy in building an image is carried out by evaluating public behavior, identifying policies and procedures of the organization with the public's wishes, and planning and establishing an action program so that the public can accept and understand the program held by the school.